Toxicity induced by dieldrin and chlorpyrifos in the freshwater crayfish Cambarellus montezumae (Cambaridae) - Díaz-Barriga, Sandra (2015)
The toxicity induced by insecticides in aquatic organisms is of utmost relevance because it may give a clue about the degree of health or damage of the involved ecosystem. In the present report, we determined the effect of dieldrin (DD) and chlorpyrifos (CP) on the freshwater crayfish, Cambarellus montezumae. The organisms (4-6cm in diameter) were collected in the Ignacio Ramírez Reservoir, situated at 50km Northeast of Mexico City, in the Rio Lerma Basin. Initially, we determined the LC50 value with the Probit method, then the DNA damage with single cell gel electrophoresis (comet assay applied at 24, 48, and 72h of exposure) applied to the brain and hepatopancreas of animals exposed (in reconstituted water) to 0.05 and 0.5mg/L of each insecticide. In the hepatopancreas of the same organisms, we determined the lipid peroxidation by applying the TBARS test. DNA damage and lipid peroxidation were also evaluated with the same methods to organisms exposed in water from the reservoir. In regard to the LC50, at 72h of exposure, we found a value of 5.1mg/L and a value of 55.62mg/L for DD and CP, respectively. The comet assay applied at different exposure times showed significant DNA damage to both organs, with respect to the control level. In the case of DD, statistical significance was observed for the two doses in the whole evaluated schedule. CP was genotoxic in the brain with the high dose at 72h, and in the hepatopancreas with the two tested doses at all evaluated exposure times. Also, a significant lipid peroxidation increase was detected with the two doses of insecticides. In the study with water from the reservoir, a more pronounced DNA damage was detected. Our results showed strong DNA damage induced by both insecticides in the crayfish, as well as a correlation with the lipid peroxidation effect, suggesting that oxidative stress is involved in the genotoxic alteration. Our results also showed the usefulness of the studied organism as well as the applied tests for the evaluation of toxicological effects, and suggested the pertinence of applying the comet assay to other freshwater organisms to evaluate the bioaccumulation of insecticides.   1,3Sandra Díaz-Barriga, 2Laura Martínez-Tabche, 3Isela Álvarez-González, 3Eduardo Madrigal-Bujaidar*, 4Eugenia López-López.1Laboratorio de Genética, Facultad de Estudios Superiores Cuautitlán. UNAM.2Laboratorio de Toxicología Acuática, Escuela Nacional de Ciencias Biológicas, IPN.3Laboratorio de Genética, Escuela Nacional de Ciencias Biológicas IPN.4Departamento de Zoología, Escuela Nacional de Ciencias Biológicas IPN.México